COMPARISON OF JENKINS AND GITLAB CI/CD TO IMPROVE DELIVERY TIME OF BASU DAIRY FARM ADMIN WEBSITE - Kuncara, Alif Babrizq; Kusumo, Dana Sulistyo; Adrian, Monterico (Jurnal Teknik Informatika (Jutif), 2024)
The Basu Dairy Farm admin website is a web-based information system developed using monolithic architecture. The delivery process of source code changes from the GitLab repository on the "main" branch (development) to the main server (production) takes a long time because the build and deploy process is done manually. This causes the delivery time to be long. To overcome this, this research applies Continuous Integration/Continuous Deployment (CI/CD) as a solution. The CI/CD tools used are Jenkins and GitLab CI/CD because they are open source and the most popular. In this study, a comparison of the delivery time of the two tools was carried out. Delivery time is obtained when the build process starts to run until the deploy process is completed. The analysis includes the time required to run the build and deploy process of the CI/CD tool. The results of this research show that Jenkins and GitLab CI/CD are successfully implemented and can automate the build and deploy process. In terms of implementation, Jenkins requires in-depth configuration, so it looks complicated, while GitLab CI/CD offers simple and easy configuration. In the three experiments conducted, Jenkins showed a faster average time in completing the build and deploy process, so Jenkins has a better delivery time than GitLab CI/CD in the context of the Basu Dairy Farm admin website development process.